The Race to Retain Healthcare Workers: A Systematic Review on Factors that Impact Retention of Nurses and Physicians in Hospitals - Neeltje de Vries RN, MSc; Anke Boone MSc; Lode Godderis MD, PhD; José Bouman BEd; Szymon Szemik PhD; Domenica Matranga PhD; Peter de Winter MD, PhD (SAGE Publishing, 2023)
The shortage of healthcare workers is a growing problem across the globe. Nurses and physicians, in particular, are vulnerable as a result of the COVID-19 pandemic. Understanding why they might leave is imperative for improving retention. This systematic review explores both the prevalence of nurses and physicians who are intent on leaving their position at hospitals in European countries and the main determinants influencing job retention among nurses and physicians of their respective position in a hospital setting in both European and non-European countries. A comprehensive search was fulfilled within 3 electronic databases on June 3rd 2021. In total 345 articles met the inclusion criteria. The determinants were categorized into 6 themes: personal characteristics, job demands, employment services, working conditions, work relationships, and organizational culture. The main determinants for job retention were job satisfaction, career development and work-life balance. European and non-European countries showed similarities and differences in determinants influencing retention. Identifying these factors supports the development of multifactorial interventions, which can aid the formulation of medical strategies and help to maximize retention.